Multi‐Resonant Thermally Activated Delayed Fluorescent (MR‐TADF) Compounds as Photocatalysts. Issue 2 (14th November 2022) - Prentice, Callum; Morrison, James; Smith, Andrew D.; Zysman‐Colman, Eli
Abstract: Donor‐acceptor (D−A) thermally activated delayed fluorescent (TADF) compounds, such as 4CzIPN, have become a widely used sub‐class of organic photocatalysts for a plethora of photocatalytic reactions. Multi‐resonant TADF (MR‐TADF) compounds, a subclass of TADF emitters that are rigid nanographene derivatives, such as DiKTa and Mes3 DiKTa, have to date not been explored as photocatalysts. In this study both DiKTa and Mes3 DiKTa were found to give comparable or better product yield than 4CzIPN in a range of photocatalytic processes that rely upon reductive quenching, oxidative quenching, energy transfer and dual photocatalytic processes. In a model oxidative quench process, DiKTa and Mes3 DiKTa gave increased reaction rates in comparison to 4CzIPN, with DiKTa being of particular interest due to the lower material cost (£0.94/mmol) compared to that of 4CzIPN (£3.26/mmol). These results suggest that DiKTa and Mes3 DiKTa would be excellent additions to any chemist's collection of photocatalysts. Abstract : Multi‐resonant thermally activated delayed fluorescence (MR‐TADF) compounds, DiKTa and Mes3 DiKTa, are shown to be excellent photocatalysts in a range of different reactions, benchmarked against the widely used donor‐acceptor TADF photocatalyst, 4CzIPN . Advantages of using these MR‐TADF photocatalysts include robust and inexpensive photocatalyst synthesis, lower required photocatalyst loadings and faster reaction rates, while achieving comparable or improved product yields.